“I wanna play Powerchair Hockey until I die”: The performance of the value of life through the social organization of death in sport - Paccaud, Laurent (Current Issues in Sport Science (CISS), 2023)
Introduction Powerchair Hockey (PCH) is one of the few team sports available for electric wheelchair users. In Switzerland, the majority of PCH players are living with degenerative diseases (neuromuscular diseases). Their life expectancy is usually no more than 30 years. Nevertheless, although their physical impairments gradually worsen, most players keep on playing sport until they die. Thus, while death is usually a taboo in our society (Elias, 1987), it is an inherent dimension of PCH. Players’ deaths are collectively organized through rituals. Aims In this presentation, I investigate how the social organization of death in PCH shapes the “status passage” (Glaser & Strauss, 1971) that represent the experience of death. More specifically, what does the players’ deaths reveal about the value of their sports commitment, and, more broadly, their life? Methods The study is based on a 4 years multi-sited ethnography (Marcus, 1995) of Powerchair Hockey in French- and German-speaking Switzerland. Different tools have been used to collect data: participant observation, life narrative interviews, photo-elicitation interviews, and archival research and consultation. A thematic analysis was performed on the data set (Paillé & Mucchielli, 2012). Results and discussion The analyses show that, in the daily lives of people living with neuromuscular diseases, death is a taboo. PCH proves to be one of the few social arenas where players have the opportunity to talk about it. The collective management of death by those involved in PCH has two main outcomes: (1) the celebration of the live, accomplishments and legacy of the player who died, (2) the preparation of other players to their own death, which may be approaching. For PCH players, carrying on with their sport commitment until the very end of their lives shapes their “transition to death” (Glaser & Strauss, 1971) significantly. Indeed, being part of a sport that outlasts them and being memorialized during and after death, they become part of the history of the community. This contrasts with the fact that, in other areas of their lives (the specialized institutions, the social insurances, the medical world), their lives may be considered to have little value. Thus, the mortuary rituals and the legacy that players leave are performative of the value of their lives. This contributes to their “grievability” (Butler, 2009; i.e., the recognition of the worthiness of their lives). References Butler, J. (2009). Frames of War: When Is Life Grievable? Verso. Elias, N. (1987). La solitude des mourants [The loneliness of the dying].Bourgois. Glaser, B., & Strauss, A. (1971). Status passage: A formal theory. Aldine. Marcus, G. E. (1995). Ethnography in/of the world system: The emergence of multi-sited ethnography. Annual Review of Anthropology, 24(1), 95-117. https://doi.org/10.1146/annurev.an.24.100195.000523 Paillé, P., & Mucchielli, A. (2012). L’analyse qualitative en sciences humaines et sociales [Qualitative analysis in the humanities and social sciences]. Armand Colin.